Análise do genoma de isolados citopáticos do vírus da diarréia viral bovina (BVDV) para rearranjos genômicos associados com a expressão da proteína NS3. - Quadros, Valter Leonardo de (2005)
Calves born persistently infected (PI) with non-cytopathic bovine viral diarrhea virus (ncpBVDV) frequently develop a fatal gastroenteric illness called mucosal disease (MD). From animals affected by MD, both the original virus (ncpBVDV) and an antigenically identical, yet cytopathic virus (cpBVDV) can be isolated. Cytopathic BVDVs are originated from the ncp counterparts by diverse genetic mechanisms, all leading to the expression of the non-structural polypeptide NS3 as a discrete protein. In contrast, ncpBVDVs express only the large precursor polypeptide, NS2-3, which contains the NS3 sequence within its carboxy-terminal half. The investigation of the mechanism leading to NS3 expression in 41 cpBVDV isolates is reported. An RT-PCR strategy was designed to detect insertions within the NS2-3 gene and/or duplication of the NS3 gene two common mechanisms of expression of NS3. RT-PCR amplification revealed insertions in the NS2-3 gene of three cp isolates, being the inserts similar in size to that present in the cpBVDV NADL strain. Sequencing of one such insert revealed a 296 nucleotide sequence, with a central core of 270 putative aminoacid sequence highly homologous (98%) to the NADL insert, a sequence corresponding to the cellular J-Domain gene. Another cpBVDV isolate contained a duplication of the NS3 gene downstream from the original locus. In contrast, no detectable NS2-3 insertions nor NS3 gene duplications were observed in the genome of 37 cp isolates. These results demonstrate that cleavage of NS2-3 without bulk RNA insertions nor NS3 gene duplications seems to be a frequent mechanism leading to NS3 expression and BVDV cytopathology.